DEIXIS ANALYSIS IN A FOX NEWS INTERVIEW WITH PRESIDENT DONALD TRUMP - Camelia Camelia; Julia Azzahra; Paulline Dona Shiva Latumahina; Cecep Agus (Linguistik : Jurnal Bahasa dan Sastra, 2026)
This study investigates the use of deixis in a political interview broadcast on Fox News featuring U.S. President Donald Trump. Deixis is central to political discourse because it links language to context and helps speakers position themselves, others, and events. The objective of this research is to identify the types of deictic expressions used in the interview and to explain their pragmatic functions based on Levinson’s (1983) theory. Using a qualitative descriptive method, data were collected from the interview transcript and analyzed. The findings indicate that person deixis is the most dominant type, especially “I” and “we” which express authority, responsibility, and solidarity, while third-person forms “they” and “them” create distance and opposition. Time, place, discourse, and social deixis support narrative framing, argument organization, and the expression of power relations. This study shows that deixis functions as a strategic linguistic resource in constructing political meaning and ideological positioning in media discourse.